Mitos Asmat "Fumiripits" dalam Kajian Antropologi Sastra - Ummu Fatimah Ria Lestari (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
This research discusses about Asmat myth “Fumiripits” in Anthropological Literary Study. The problem is how the structure of Asmat myths “Fumiripits” in Anthropological Literary Study is. This research used descriptive-analytical method. This method is used in social researches to systematically and accurately describe facts and characteristics of certain population. in its techniques, the researcheranalyzed its intrinsic and extrinsic elements in Asmat myth “Fumiripits” so Anthropological componentsin oral and text of Asmat myth “Fumiripits” could be found. The Asmat philosophical concept showsthat the myth “Fumiripits” is the story of their origin. Finally, the researcher concludes that anthropological literary study can be applied in myths research.